PENGARUH NAUNGAN TERHADAP PERTUMBUHAN BIBIT PULAI {Alstonia scholaris (L.) R.Br) - Juhaeti, Titi (BERITA BIOLOGI, 2009)
Pulai {Alstonia scholaris (L.) R.Br famili Apocynaceae} is one of the prospective plants due to its multipurpose such as for construction, medicine and handicraft. It is known that pulai can be propagated by seed, cutting or grafting. To have the best performance of seedling in the nursery, we have to study many aspects. One of that aspect is shading tolerance of pulai seedling. This research was conducted to study the effect of 0, 25, 50 and 75% shading on the growth of pulai seedling. The result showed that the best growth of pulai seedlings is on the 0% shading. But in 25-50% shading the growth of pulai seedling are still in good performance, while in 75% of shading the growth have been decreased.